2019
DOI: 10.2298/jmmb190520051t
|View full text |Cite
|
Sign up to set email alerts
|

Fluidized bed roasting technology in iron ores dressing in China: A review on equipment development and application prospect

Abstract: Due to the undesirable characteristics of iron ore resources in China, it is necessary to utilize refractory iron ores resources with high efficiency. The mining and mineral processing costs are usually high. The supply of domestic iron ores in China has been in serious shortage for a long time. Therefore, the development and utilization of complex and refractory iron ore resources are extremely urgent. Magnetizing roasting followed by magnetic separation is an important method for the beneficiation of low gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 29 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…They performed a Vibrating Sample Magnetometer (VSM) test on the concentrate and found that greater magnetism causes better enrichment. Tang et al [50] pointed out that fluidized roasting in traditional pyrometallurgy has the advantages of fast reaction speed, rapid mass transfer, low energy consumption and uniform temperature. If the reaction is carried out in a fluidized bed with a gas reductant, the reaction temperature and reaction time can be further reduced.…”
Section: Pyrometallurgical Methodsmentioning
confidence: 99%
“…They performed a Vibrating Sample Magnetometer (VSM) test on the concentrate and found that greater magnetism causes better enrichment. Tang et al [50] pointed out that fluidized roasting in traditional pyrometallurgy has the advantages of fast reaction speed, rapid mass transfer, low energy consumption and uniform temperature. If the reaction is carried out in a fluidized bed with a gas reductant, the reaction temperature and reaction time can be further reduced.…”
Section: Pyrometallurgical Methodsmentioning
confidence: 99%
“…It can convert weakly magnetic minerals into strongly magnetic minerals and thus improving the separability of LGRIO (Sun et al, 2020;Yu et al, 2017). Moreover, several economical and effective roasting technologies for LGRIO have emerged, such as flash roasting, low-temperature roasting, and so on (Boehm et al, 2014;Wan et al, 2022;Pinto et al, 2022;Tang et al, 2019). However, studies on the nature of roasted products and the dissociation and magnetic separation of fine, complex, and highly disseminated types of iron ore have seldom been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Iron ores are scattered in all parts of China with verified ore reserves of about 80 billion tons, but most reserves are low in grade with an average grade of 30.5% total iron (Li et al, 2015;Tang et al, 2019). 1.70 billion tons of these proven reserves are located in the Southern Anshan area in Liaoning Province, which is equivalent to reserves of 0.68 billion tons with an average grade of 34% total iron (Li et al, 2015).…”
Section: Introductionmentioning
confidence: 99%